Calystegines in potatoes with genetically engineered carbohydrate metabolism - Sonnewald, Uwe; et al. (Journal of Experimental Botany, 2007)
Calystegines are hydroxylated nortropane alkaloids derived from the tropane alkaloid biosynthetic pathway. They are strong glycosidase inhibitors and occur in vegetables such as potatoes, tomatoes, and cabbage. Calystegine accumulation in root cultures was described to increase with carbohydrate availability. Whether this is indicative for the in planta situation is as yet unknown. Potatoes are model plants for the study of carbohydrate metabolism. Numerous transgenic potato lines with altered carbohydrate metabolism are available, but rarely were examined for alterations in secondary metabolism. In this study, calystegine accumulation and expression of biosynthetic enzymes were related to genetic modifications in carbohydrate metabolism in potato tubers. Tubers contained more so uble sugars due to overexpression of yeast invertase in the apoplast or in the cytosol, or due to antisense suppression of sucrose synthase. It is shown that the major part of calystegines in tubers originated from biosynthesis in plant roots. Yet, tuber calystegine levels responded to genetic alterations of carbohydrate metabolism in tubers. The strongest increase in calystegines was found in tubers with suppressed sucrose synthase activity. Transcripts and enzyme activities involved in calystegine biosynthesis largely concurred with product accumulation. Whole plant organs were examined similarly and displayed higher calystegines and corresponding enzyme activities in roots and stolons of plants with enhanced soluble sugars. Increases in calystegines appear to be linked to sucrose availability.
Keywords: antisense; calystegine; carbohydrate metabolism; invertase; overexpression; potato; sucrose synthase; tropane alkaloid biosynthesis